Activation of FGFR2 Signaling Suppresses BRCA1 and Drives Triple‐Negative Mammary Tumorigenesis That is Sensitive to Immunotherapy. Issue 21 (13th September 2021) - Lei, Josh Haipeng; Lee, Mi‐Hye; Miao, Kai; Huang, Zebin; Yao, Zhicheng; Zhang, Aiping; Xu, Jun; Zhao, Ming; Huang, Zenan; Zhang, Xin; Chen, Si; Jiaying, NG; et al.
Abstract: Fibroblast growth factor receptor 2 (FGFR2) is a membrane‐spanning tyrosine kinase that mediates FGF signaling. Various FGFR2 alterations are detected in breast cancer, yet it remains unclear if activation of FGFR2 signaling initiates tumor formation. In an attempt to answer this question, a mouse model berrying an activation mutation of FGFR2 (FGFR2‐S252W) in the mammary gland is generated. It is found that FGF/FGFR2 signaling drives the development of triple‐negative breast cancer accompanied by epithelial‐mesenchymal transition that is regulated by FGFR2‐STAT3 signaling. It is demonstrated that FGFR2 suppresses BRCA1 via the ERK‐YY1 axis and promotes tumor progression. BRCA1 knockout in the mammary gland of the FGFR2‐S252W mice significantly accelerated tumorigenesis. It is also shown that FGFR2 positively regulates PD‐L1 and that a combination of FGFR2 inhibition and immune checkpoint blockade kills cancer cells. These data suggest that the mouse models mimic human breast cancers and can be used to identify actionable therapeutic targets. Abstract : In this study, it is demonstrated that activation of FGFR2 promotes triple‐negative breast cancer formation through regulating expression of BRCA1 negatively and PD‐L1 positively. Inhibition of FGFR2, which is widely expressed in human breast cancers, can be combined preclinically with immune checkpoint antibodies to enhance anticancer immunotherapy, warranting clinical evaluation of personalized targeted therapy.